How to cook everything. The basics : all you need to make great food - Bittman, Mark (Wiley, 2012)
"From dicing vegetables and roasting meat, to cooking building-block meals that include salads, soups, poultry, meats, fish, sides, and desserts, Bittman explains what every home cook, particularly novices, should know.More than 1,000 beautiful and instructive photographs throughout the book reveal key preparation details that make every dish inviting and accessible."--